PENGARUH PERMAINAN TRADISIONAL BOY-BOYAN TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI TK BAKTI IBU KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Desnawati Desnawati; Ria Novianti; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is aimed 1) to find out the ability of rough motorik of the children in TK bakti ibu pekanbaru before were given treatment like boy boyan traditional game, 2) to find out the ability of rough motorik of the children in TK bakti ibu pekanbaru after were given treatment like boy boyan traditional game, to find out whether the boy boyn traditional game affected on the children in TK bakti ibu pekanbaru. This research was an experimental research that was a research that aimed to know the effect of one variable to other variable in a strictly controlled condition. The sample of this research were all the students that 4-5 th years old in class B2 that consist of 15 children, that was 7 male and 8 female. The collective data technique was an observation and documentation. So the result of this research were 1) the rough motorik ability of the 4-5 th years old children before given treatment like boy boyan traditional game is in developing category, 2) the rough motorik ability of the 4-5 th years old children after were given treatment like boy boyan traditional game is in developing category as expected, 3) there is a significant effect on the boy boyan traditional game to the ability of rough motorik of the children in TK bakti ibu pekanbaru. It is known that there is difference that an improving ability of rough motorik to children before and after treatment. Traditional boy boyan game has an effect as 66,66% on the 4-5 th years old children in TK bakti ibu pekanbaru.Key words: Boy boyan traditional game, rough motorik